I am enough - Byers, Grace (New York Balzer + Bray, 2018)
Shares a story of loving who you are, respecting others and being kind to one another.
ALA Booklist
Bulletin(Center for Children's Books)
Horn Book
Kirkus Reviews
2
P-2
Keywords: Self-acceptance -- Juvenile fiction; Bullying -- Juvenile fiction; Self-esteem -- Juvenile fiction